UJI KADAR ABU PAKAN TERNAK DAERAH KABUPATEN SIJUNJUNG DENGAN METODE GRAVIMETRI - Komala Sari, Irma Septia (Biology Department, Mathematics and natural science, Tadulako University, 2024)
Feed is anything that can be given as a source of energy and nutrients. The organic matter content of a feed depends on other components such as dry matter and ash. Gravimetry is a quantitative analysis used to determine the total ash content. This experiment used a completely randomized design. Based on the observation table which presents many samples in Sijunjung, feed samples processed from various different brands meet good nutritional standards for animal nutrition according to SNI standards.